The cultural and historical significance of malopo ritual: a Pedi perspective - M. E. K. Lebaka (Acta Theologica)
Indeed, the implicit hypothesis that “there is little possibility, if any, for the Pedi traditional healers to experience the supernatural form of healing without performing music and dancing to it” raises the issue of “What makes the dance potent as a healing therapy?” or ‘What is the role of music in such healing processes?’. This article is a result of a guided investigation carried out in order to answer these questions. The primary sources for data collection were literature reviews, informal interviews, observations and recordings. During the study, informal discussions with traditional healers and their trainees revealed that participation in malopo rituals enables community members to inherit their music tradition. The impression created during interviews and observations was that Pedi traditional healers perform malopo songs to communicate with the ancestors. The results suggest that malopo rituals are aimed at enriching the personal and social life of the Pedi community.